2017
DOI: 10.1002/hbm.23596
|View full text |Cite
|
Sign up to set email alerts
|

Tired and misconnected: A breakdown of brain modularity following sleep deprivation

Abstract: Sleep deprivation (SD) critically affects a range of cognitive and affective functions, typically assessed during task performance. Whether such impairments stem from changes to the brain's intrinsic functional connectivity remain largely unknown. To examine this hypothesis, we applied graph theoretical analysis on resting-state fMRI data derived from 18 healthy participants, acquired during both sleep-rested and sleep-deprived states. We hypothesized that parameters indicative of graph connectivity, such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…Experimentally induced SD has been associated with altered cognitive and emotional functioning, including impaired executive control, working memory, and attention ( Anderson and Platten, 2011 ; Ma et al , 2015 ; Scott et al , 2006 ), as well as increased negative emotionality which has been associated with impaired interaction between the amygdala and medial prefrontal regions suggesting deficient prefrontal-top down control of amygdala emotional reactivity ( Ben Simon et al , 2017 ; Lei et al , 2015 ; Motomura et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally induced SD has been associated with altered cognitive and emotional functioning, including impaired executive control, working memory, and attention ( Anderson and Platten, 2011 ; Ma et al , 2015 ; Scott et al , 2006 ), as well as increased negative emotionality which has been associated with impaired interaction between the amygdala and medial prefrontal regions suggesting deficient prefrontal-top down control of amygdala emotional reactivity ( Ben Simon et al , 2017 ; Lei et al , 2015 ; Motomura et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Network hierarchy is one of probably several other metrics that might capture dynamics in network organization with respect to changes in emotional experience. Further studies should test different network features which have been shown to be sensitive to emotional brain states such as network integration (Kinnison et al, 2012 ) or modularity (Ben Simon et al, 2017 ) during the anger experience. It should also be noted that while D EP NA can be used to make inferences regarding the influence hierarchy within a network, it does not infer a causal influence in the true sense, as correlation does not imply causation (Friston, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Support for this proposition comes from numerous resting state fMRI studies, suggesting that sleep deprivation triggers a breakdown in network integrity that may negatively affect, and possibly predict, task related responses in this condition (Krause et al, 2017). For example, a graph theoretical analysis applied on a resting state fMRI data obtained from the currently tested cohort showed that under conditions of sleep deprivation, network architecture shifts towards a more random-like organization, leading to impaired functional segregation in regions of the limbic, salience and default mode networks (Ben Simon et al, 2017). These alterations were further associated with impaired task performance elicited by sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%